Teachers’ view about the current situation of e-learning practice in undergraduate medical education of Bangladesh - Talukder, MAS; Talukder, Md Humayun Kabir; Pervin, MR; Talukder, MFH; Tapu, TT (Bangladesh Journal of Medical Education, 2020)
Background: E-learning or electronic learning is increasingly used as a complement to traditional classes in undergraduate medical education. E-Learning become more popular, because they allow saving time of teachers and students, reduce costs of teaching and learning materials and improve classroom as well as medical colleges’ educational environment. Objectives: This descriptive cross sectional survey was driven to explore teachers’ view about the current situation of e-learning practice in undergraduate medical education of Bangladesh. Methods: From all four phases, total 172 teachers of randomly selected eight medical colleges of Bangladesh were respondents of this study to seek information regarding the current situation of e-learning practice in undergraduate medical education, between the period of July 2018 to June 2019 with a pretested self-administered questionnaire. Results: In this study 68 (39.5%) were male and 104 (60.5%) were female teachers. Fifty-two point three percent (52.3%) teachers agreed that they strongly awared of e-learning, 87.8% teachers had personal computers/laptops, 99.4% teachers had personal smartphones, and 98.8% teachers had personal e-mail addresses. Fifty-three percent (53%) teachers agreed that they have adequate knowledge and skill in information and communication technology (ICT). Forty-four percent (44%) teachers disagreed that they were interact with students and 49.5% teachers agreed that they interacted with peer and colleague by using social media in their medical colleges. Conclusion: Teachers are aware of e-learning and they practiced it in personal level without collaboration of the medical colleges. It is essential to provide e-learning facilities in medical colleges for improvement of undergraduate medical education. Bangladesh Journal of Medical Education Vol.11(1) 2020: 12-16